Accuracy of Depression Screening Tools to Detect Major Depression in Children and Adolescents: A Systematic Review. (December 2016) - Roseman, Michelle; Kloda, Lorie A.; Saadat, Nazanin; Riehm, Kira E.; Ickowicz, Abel; Baltzer, Franziska; Katz, Laurence Y.; Patten, Scott B.; Rousseau, Cécile; Thombs, Brett D.
Objective: Depression screening among children and adolescents is controversial, and no clinical trials have evaluated benefits and harms of screening programs. A requirement for effective screening is a screening tool with demonstrated high accuracy. The objective of this systematic review was to evaluate the accuracy of depression screening instruments to detect major depressive disorder (MDD) in children and adolescents. Method: Data sources included the MEDLINE, MEDLINE In-Process, EMBASE, PsycINFO, HaPI, and LILACS databases from 2006 to September 30, 2015. Eligible studies compared a depression screening tool to a validated diagnostic interview for MDD and reported accuracy data for children and adolescents aged 6 to 18 years. Risk of bias was assessed with QUADAS-2. Results: We identified 17 studies with data on 20 depression screening tools. Few studies examined the accuracy of the same screening tools. Cut-off scores identified as optimal were inconsistent across studies. Width of 95% confidence intervals (CIs) for sensitivity ranged from 9% to 55% (median 32%), and only 1 study had a lower bound 95% CI ≥80%. For specificity, 95% CI width ranged from 2% to 27% (median 9%), and 3 studies had a lower bound ≥90%. Methodological limitations included small sample sizes, exploratory data analyses to identify optimal cut-offs, and the failure to exclude children and adolescents already diagnosed or treated for depression. Conclusions: There is insufficient evidence that any depression screening tool and cut-off accurately screens for MDD in children and adolescents. Screening could lead to overdiagnosis and the consumption of scarce health care resources.